Hukum Molo Batu: Bentuk Penyelesaian Sengketa Dalam Kelompok Masyarakat Ada - Noya, Ekberth Vallen (BAMETI Customary Law Review, 2024)
A customary law community is an arrangement of customary law associations whose members are bound by territorial and genealogical factors. Legal experts in the Dutch East Indies era gave the understanding that a territorial customary law community was a permanent and orderly community, which was bound to a certain area, both in worldly terms as a place of life and in spiritual terms as a place of worship for ancestral spirits. . Recognition and respect for the existence of customary justice can be seen through article 18 B paragraph 2 of the 1945 Constitution. Article 18 B paragraph 2 of the 1945 Constitution. The State recognizes and respects customary law community units and their traditional rights as long as they are still alive and in accordance with the development of society and principles of the Unitary State of the Republic of Indonesia, which are regulated in law. The law of Molo (Diving) Batu is a custom of indigenous peoples that occurs in Hulaliu Country, Huaruku Island District. Molo Batu is a traditional procession to resolve land boundary disputes. Usually the Molo Batu procession is the end of the stages taken by the traditional institutions of Hulaliu Country, where the procession resolves land disputes. is the same as traditional institutions in general, where it starts with mediation, gathering evidence, reviewing the location or what is usually called pulling the chain (chain) at the boundary, decision making by Upu Pati Launusa (King) and Saniri, if one party feels they are not benefiting then will continue with the Molo Batu customary law.